Whole Genome Sequencing of Escherichia coli From Store-Bought Produce - Reid, Cameron J.; Blau, Khald; Jechalke, Sven; Smalla, Kornelia; Djordjevic, Steven P. (Frontiers in Microbiology, 2020)
The role of agriculture in the transfer of drug resistant pathogens to humans is widely debated and poorly understood. Escherichia coli is a valuable indicator organism for contamination and carriage of antimicrobial resistance in foods. Whilst whole genome sequences for E. coli from animals and associated meats are common, sequences from produce are scarce. Produce may acquire drug resistant E. coli from animal manure fertilizers, contaminated irrigation water and wildlife, particularly birds. Whole genome sequencing was used to characterize 120 tetracycline (TET) resistant E. coli from store-bought, ready-to-eat cilantro, arugula and mixed salad from two German cities. E. coli were recovered on the day of purchase and after 7 days of refrigeration. Cilantro was far more frequently contaminated with TET resistant E. coli providing 102 (85%) sequenced strains. Phylogroup B1 dominated the collection (n=84, 70%) with multi-locus sequence types B1-ST6186 (n=37, 31%), C-ST165 (n=17, 14%), B1-ST58 (n=14, 12%), B1-ST641 (n=8, 7%) and C-ST88 (n=5, 4%) frequently identified. Notably, seven strains of diverse ST carried genetic indicators of ColV virulence plasmid carriage. A number of previously identified and novel integrons associated with insertion elements including IS26 were also identified. Storage may affect the lineages of E. coli isolated however further studies are needed. Our study indicates produce predominantly carry E. coli with a commensal phylogroup and a variety of antimicrobial resistance and virulence-associated traits. Genomic surveillance of bacteria that contaminate produce should be a matter of public health importance in order to develop a holistic understanding of the environmental dimensions of antimicrobial resistance.